Suicide attempts in children and adolescents – risk factors, methods and management of suicidal patient - Marzec, Izabela; Zabłocka, Katarzyna; Stachurski, Jan (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Suicide is a major public health problem that affects people of all ages, including children. A child’s decision to commit suicide is influenced by many social and psychological factors, as well as mental illness and addiction. Aim of this paper is to discuss the large scale of suicidal behaviors among children and adolescents, to select the most common causes and methods of suicide and to present a practical approach to the problem. For this purpose comprehensive review of the literature has been conducted. The most common suicide methods among children and adolescents are: hanging, jumping from a height and poisoning. According to the existing studies, quick reaction in the event of a suicide attempt is essential. The key to life-saving moment is a proper guidance of the child in the emergency department. Children after suicide attempts require long-term care, in which many people are involved like doctors, nurses and parents.